A practical approach for preventing dispersion of infection disease in naturally ventilated room. (1st May 2022) - Ren, Chen; Cao, Shi-Jie; Haghighat, Fariborz
Abstract: During the ongoing COVID-19 pandemic period, the airborne transmission of viruses has raised widespread concern as daily activities are resumed in public buildings. It is essential to develop mitigation strategies of infection disease transmission (e.g., increase of ventilation rate) in different scenarios to reduce the infection risk. For classrooms in schools, natural ventilation is generally used to provide outdoor air into rooms. However, the supply air volume depends strongly on the local conditions, e.g., window opening size and outdoor wind speed. In this study, the optimal design of classroom window openings is investigated, based on which low-cost window-integrated fans are then employed to enhance the efficiency of natural ventilation and infection disease control. Taking infected students as pollutant sources, numerical simulations are carried out to predict the pollutant concentration under various scenarios of pollutant sources and window opening modes (with/without fans), and to calculate the infection risk. It is found that by redesigning window openings, the airflow distribution performance index (ADPI) can be increased by 17% with corresponding infection likelihood decreased by 27%. The window-integrated fan has a significant effect on improving ventilation performance and prevention of infection disease transmission, leading to an ADPI of 99% and minimum infection probability of 11% for students sitting near the windows. This work can help to develop low-cost and effective mitigating measures of infection disease in classrooms by using hybrid ventilation systems. Graphical abstract: Image 1 Highlights: The mitigation of infection disease transmission was explored in classrooms. Optimal design of window openings and window-integrated fans were investigated. The window-integrated fans had great impact on improving ventilation performance. The prevention of infection disease transmission was improved by using fans.